Is the Optic Nerve Head Structure Impacted by a Diagnostic Lumbar Puncture in Humans?. Issue 11 (November 2017) - Poli, Muriel; Denis, Philippe; Sellem, Eric; Aho-Glélé, Ludwig-Serge; Bron, Alain M.
Abstract : Purpose: The purpose of this study is to assess in vivo whether diagnostic lumbar puncture (LP) is followed by optic nerve head (ONH) and parapapillary anatomic changes in normal human eyes. Materials and Methods: Prospective, single-center, observational case series. ONH structures (prelaminar tissue surface, anterior surface of the lamina cribrosa, central retinal vessels) and parapapillary structures (internal limiting membrane, posterior surfaces of retinal nerve fiber layer and Bruch membrane/retinal pigment epithelium complex, Bruch membrane opening, posterior surface of the choroid) were quantitatively evaluated by means of swept-source optical coherence tomography (Triton Ver.10.05, Topcon, Tokyo, Japan) before and after LP (5, 60, and 360 min). Each of these structures was manually delineated for measurement before being superimposed to detect any displacement, using peripheral margins of parapapillary structures as a reference plane. Results: A total of 16 eyes of 8 nonglaucomatous patients were evaluated. The CSF volume was median (IQR), 1.65 mL (1.16 to 2.00) and none of the ONH structures showed any anatomic changes at any time point after LP. Conclusions: According to the design of this study, diagnostic LP is a safe procedure regarding deep ONH structures in nonglaucomatous subjects.